Twenty-year Longitudinal Follow-up MRI Study of Asymptomatic Volunteers: The Impact of Cervical Alignment on Disk Degeneration. Issue 10 (December 2018) - Okada, Eijiro; Daimon, Kenshi; Fujiwara, Hirokazu; Nishiwaki, Yuji; Nojiri, Kenya; Watanabe, Masahiko; Katoh, Hiroyuki; Shimizu, Kentaro; Ishihama, Hiroko; Fujita, Nobuyuki; Tsuji, Takashi; Nakamura, Masaya; et al.
Abstract : Study Design: A 20-year longitudinal study. Objective: To evaluate the long-term effect of sagittal alignment of the cervical spine on intervertebral disk degeneration in healthy asymptomatic subjects. Summary of Background Data: This study continues a previous 10-year longitudinal study to determine whether sagittal alignment affects disk degeneration during normal aging. Materials and Methods: We assessed 90 healthy subjects (30 men and 60 women) from among 497 volunteers who underwent magnetic resonance imaging (MRI) and plain radiographs of the cervical spine between 1994 and 1996 (follow-up rate 18.1%). The mean age at the initial study was 35.5±13.4 years (11–65 y). We compared initial MRIs and follow-up MRIs, conducted at an average of 21.6 years after the initial study, for (1) decreased signal intensity of the intervertebral disks, (2) posterior disk protrusion, and (3) disk-space narrowing from C2–3 to C7–T1. Subjects were grouped by age at follow-up (under 40 vs. 40 y and older) and by a lordotic or nonlordotic cervical sagittal alignment at baseline. We assessed neck pain, stiff shoulders, and upper-arm numbness at follow-up, and examined associations between clinical symptoms and MRI parameters. Results: Progressive changes during the 20-year period included a decrease in disk signal intensity (84.4% of subjects), posterior disk protrusion (86.7%), and disk-space narrowing (17.8%). No significant association was observed between sagittal alignment and decreased disk signal intensity, posterior disk protrusion, or disk-space narrowing. Among subjects over the age of 40, progressive degenerative changes at C7–T1 were significantly more frequent in nonlordotic subjects (90.9%) compared with those with cervical lordosis (54.2%, P =0.032). The prevalence of clinical symptoms was similar in lordotic and nonlordotic subjects at follow-up. Conclusions: Nonlordotic cervical alignment was related to the progression of disk degeneration at C7–T1 but not other levels. Cervical alignment did not affect the development of clinical symptoms in healthy subjects. Level of Evidence: Level III.